Determine cable dynamic parameters from vibration measurement results - Nguyen Huu HUNG; Tran Viet HUNG (Journal of Materials and Engineering Structures)
Structural health monitoring is a particularly important issue for cable-stayed bridges. The main components of a cable-stayed bridge include the main girder, tower, and stay cables. Stay cables act as a support for the girder, helping it have a large span length. Therefore, stay cables are essential parts of cable-stayed bridges and extrados bridges. Determining the parameters of the stay cable is necessary work. Among the parameters of cable-stayed cables, dynamic parameters such as frequency and damping ratio play an important role. This paper presents a method combining the Hilbert transform and Bandpass filter to determine the frequency, damping ratio and logarithmic decrement of the stay cables. The analysis results show the logarithmic decay changes over time during the vibration. Therefore, to estimate the details, it is necessary to divide the data segment before calculating the logarithmic decay. The results of calculating the vibration frequency using the Hilbert transform method are similar to those of calculating the vibration frequency using the FFT method. The calculation results from the proposed method are compared with those of the traditional method and are highly accurate.